Problems and challenges for the Politics of Education before the change of prominence experienced by educational actors - Juan Manuel Fernández-Soria (Springer, 2013)
This paper deals with some of the problems that the Politics of Education has to face both as a subject and as a government action. Based above all on the literature appeared in specialized journals during the last five years, our attention is firstly focused on the concern for using an active methodology in the teaching of this subject which places students at the center of the teaching-learning process with the aim of encouraging their interest in its contents and inducing them to acquire civic competences. Secondly, the new but already deeply-rooted neoliberal conception of education is used to describe some of its policies, such as accountability, assessment and free choice of school. Our study finally stresses the change of prominence experienced by educational actors and calls researchers and teaching staff to face such challenges from an understanding of politics as a transforming action that seeks equality and social cohesion.